Regional and sociodemographic differences in average BMI among US children in the ECHO program. Issue 12 (31st August 2021) - Bekelman, Traci A.; Dabelea, Dana; Ganiban, Jody M.; Law, Andrew; McGovern Reilly, Alexandra; Althoff, Keri N.; Mueller, Noel; Camargo, Carlos A.; Duarte, Cristiane S.; Dunlop, Anne L.; Elliott, Amy J.; Ferrara, Assiamira; et al.
Abstract: Objective: The aim of this study was to describe the association of individual‐level characteristics (sex, race/ethnicity, birth weight, maternal education) with child BMI within each US Census region and variation in child BMI by region. Methods: This study used pooled data from 25 prospective cohort studies. Region of residence (Northeast, Midwest, South, West) was based on residential zip codes. Age‐ and sex‐specific BMI z scores were the outcome. Results: The final sample included 14, 313 children with 85, 428 BMI measurements, 49% female and 51% non‐Hispanic White. Males had a lower average BMI z score compared with females in the Midwest ( β = −0.12, 95% CI: −0.19 to −0.05) and West ( β = −0.12, 95% CI: −0.20 to −0.04). Compared with non‐Hispanic White children, BMI z score was generally higher among children who were Hispanic and Black but not across all regions. Compared with the Northeast, average BMI z score was significantly higher in the Midwest ( β = 0.09, 95% CI: 0.05 to 0.14) and lower in the South ( β = −0.12, 95% CI: −0.16 to −0.08) and West ( β = −0.14, 95% CI: −0.19 to −0.09) after adjustment for age, sex, race/ethnicity, and birth weight. Conclusions: Region of residence was associated with child BMI z scores, even after adjustment for sociodemographic characteristics. Understanding regional influences can inform targeted efforts to mitigate BMI‐related disparities among children.